Dispersion Stability of TiO2-H2O Nanofluids Containing Mixed Nanotubes and Nanosheets. (August 2015) - Shao, Xuefeng; Chen, Ying; Mo, Songping; Cheng, Zhengdong; Yin, Tao
Abstract: Titanium dioxide nanotubes (TiNTs) and nanosheets (TiNSs) were synthesized according to the hydrothermal synthesis method. TiO2 -H2 O binary nanofluids were prepared by dispersing certain amount of both TiNTs and TiNSs in deionized water. Stabilities of nanofluids of different total concentrations were observed visually 1 hour later after preparation to classify stable and unstable nanofluids among nanofluids containing different ratios of TiNTs and TiNSs. Sedimentation heights variations with time were measured to indicate sedimentation velocities of nanoparticles of nanofluids of different concentrations as well. The preliminary results revealed that binary nanofluids stabilities could be improved effectively when concentration ratios of TiNTs to TiNSs are at suitable range compared with TiNTs or TiNSs alone, otherwise stabilities were deteriorated seriously. We consider the phenomenon is possibly concerned with electrostatic repulsion and depletion interactions in binary nanofluids.